Sazonalidade no balanço de energia em áreas de cultivo de soja na Amazônia - SOUZA, Paulo Jorge de Oliveira Ponte de (2015)
It was investigated the energy balance in a soybean crop (Glycine max (L.) Merrill) grown in areas of advance of agricultural border in the Amazon. The Bowen ratio technique was used to obtain energy balance components. During the most part of the crop growing season, most of the energy was consumed as latent heat, especially during the flowering and fruiting stages. Such characteristic was related to the high leaf stomatal conductance of soybean as well as to the water availability in the region. At the harvest there was an inversion in the energy partitioning, with more energy being used for heating the air (79% of the net radiation). During the off-season there was 75% reduction in the LE and significant increase in the H (180%) compared to the values found during soybean growing season.